On influence of emissions trading on efficiency of the EU national steel sectors. Issue 3 (4th May 2021) - Zapletal, František
Abstract: Environmental policy in the European Union is a hot topic for both practitioners and researchers. Their interests are attracted mainly by the main tool of this policy—emissions trading within the EU ETS. In literature focusing on the impacts of the EU ETS, the EU is usually considered to be a compact unit and its structure is omitted there. In particular, the impacts on a single company (regardless its geographical location), on a sector of industry (regardless the member countries), or on some subset of the involved companies with respect to non-EU competitors are often explored. However, through the eyes of national governments, it is vital for the countries to keep their national industrial sectors competitive not only against companies from countries outside the EU but also from other EU countries. This paper focuses on the influence of the EU ETS on the national steel sectors in the EU and their competitiveness. The hybrid PROMETHEE-DEA approach is used to assess how the price of emission allowance and grandfathering within the EU ETS impact the technical efficiency and competitiveness of these national sectors. The results of this study show that the volatile allowance price influences the efficiency and grandfathering affects the competitiveness of the EU national steel sectors.